Grammar and Hands: Manual Turn-Taking and Its Relationships to Verbal Turn-Taking in the Transfer of Objects - Fox, Barbara; Heinemann, Trine (Frontiers in Communication, 2021)
When customers bring a material item to a shop for repair, they must make the item and its troubles inspectable to the staff at the shop. This typically requires physical manipulation of the object by the customer. For their part, the staff person may then need to take the item into their own hands to further inspect it. A physical transfer of the object from customer to staff person may thus need to be accomplished. A practical problem that can arise in such transfers is this: who has the rights and responsibilities to touch and hold the object at any given time? In our data from a shoe repair shop, this practical problem is one of turn-taking of the participants’ hands, and the participants exhibit a clear normative orientation to ‘one person touches at a time’, with gaps and overlaps being common but brief. The parallels to verbal turn-taking are explored, as are the different affordances of each semiotic resource. The data are in American English.